2011
DOI: 10.1159/000330669
|View full text |Cite
|
Sign up to set email alerts
|

Decolorizing Activity of Malachite Green and Its Mechanisms Involved in Dye Biodegradation by <i>Achromobacter xylosoxidans</i> MG1

Abstract: An Achromobacter xylosoxidans MG1 strainisolated from the effluent treatment plant of a textile and dyeing factory from Yunnan Province in China was found capable of decolorizing the malachite green dye at a high efficacy. Strain MG1 reduced 86% malachite green at the concentration of 2,000 mg/l within 1 h, representing a greater ability for decolorizing and a higher tolerance of this compound than all previously reported bacteria. Color removal was optimal at pH 6 and 38°C. Further experimental evidences demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 53 publications
1
28
2
Order By: Relevance
“…In opposite to our results, Wang et al (2011) stated that in case of Achromobacter xylosoxidans , MG1 sample agitation had no influence on triphenylmetane decolourisation. It suggests contribution of different decolourisation pathways in process.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In opposite to our results, Wang et al (2011) stated that in case of Achromobacter xylosoxidans , MG1 sample agitation had no influence on triphenylmetane decolourisation. It suggests contribution of different decolourisation pathways in process.…”
Section: Resultscontrasting
confidence: 99%
“…It suggests contribution of different decolourisation pathways in process. Current knowledge about triphenylmethane dyes decolourisation mechanisms is still in its infancy (Wang et al 2011, 2012). In study of biodegradation of triphenylmethane malachite green (MG) presented by Jang et al (2005), the triphenylomethane reductase (TMR) was shown to be responsible for the conversion of MG to colourless leucomalachite green (LMG).…”
Section: Resultsmentioning
confidence: 99%
“…was also responsible for electroacetogenesis through directly electron transfer from bacteria to electrode . Achromobacter sp., the azo dye dechlorization bacterial species, like malachite green (Wang et al, 2011), were specially enriched. However, the extracellular electron transfer capacity of Achromobacter sp.…”
Section: Bacterial Taxonomic Identification In Genus Levelmentioning
confidence: 99%
“…Achromobacter xylosoxidans MG1 strain has also been reported for malachite green decolorization. The optimum decolorization activity has been observed at pH 6.0 and 38 ∘ C in LB decolorization medium [30].…”
Section: Effect Of Temperature and Ph On Decolorizationmentioning
confidence: 94%